A Cross-current Masonry Technology for River Pole and Rock Dam in Distribution Network Maintenance and Construction. Issue 4 (May 2019) - Yong, Qian; Bin-Bin, Zhang; Chang, Lin; Xuan-Chen, Long; Ling-Hong, Chen
Abstract: Some areas of the distribution network involve the installation of line poles through seasonal ditches or channels. In the design of rock dam construction, the traditional method has great resistance to water, which reduces the service life of rock dam itself after the formation of severe scouring. In this paper, the masonry technology of rock dam is analyzed, and a kind of cross-current dam masonry technology is designed to reduce the impact of water flow, which solves the problem of rock dam damaged by the impact of water flow and extends the practical service life of rock dam greatly.